Self‐initiated use of topical cannabidiol oil for epidermolysis bullosa. Issue 4 (22nd May 2018) - Chelliah, Malcolm P.; Zinn, Zachary; Khuu, Phoung; Teng, Joyce M. C.
Abstract: Epidermolysis bullosa is a rare blistering skin disorder that is challenging to manage because skin fragility and repeated wound healing cause itching, pain, limited mobility, and recurrent infections. Cannabidiol, an active cannabinoid found in cannabis, is postulated to have antiinflammatory and analgesic effects. We report 3 cases of self‐initiated topical cannabidiol use in patients with epidermolysis bullosa in an observational study. One patient was weaned completely off oral opioid analgesics. All 3 reported faster wound healing, less blistering, and amelioration of pain with cannabidiol use. Although these results demonstrate promise, further randomized, double‐blind clinical trials are necessary to provide scientific evidence of our observed benefits of cannabidiol for the treatment of epidermolysis bullosa.